Electromagnetic Materials and Devices - Han, Man-Gui (IntechOpen, 2020)
Electromagnetic materials can be widely found in daily life, especially in electronic devices. The high-frequency properties (permittivity or permeability) of these materials strongly depend on structure, composition, shape, and orientation. Therefore, this book intends to present readers with advances not only in materials science (including metamaterials), but also in measurements and novel functional applications that demand the special properties of electromagnetic materials.